Enhancing English’ speaking skill of students in Tunas Baru High School through ICT- integrated news reporting - Pratiwi, Theodesia Lady; Togatorop, Sarah Ayuandri; Putri, Andien Aisyah; Samuel, Samuel; Zaki, Leil Badrah (Journal of English Language Teaching and Learning (JETLE), 2024)
There is an increasing importance of English speaking proficiency in today's era and there comes with challenges that students face in mastering this skill. It calls the necessity of enhancing speaking skills for 21st-century learners and proposes an innovative approach— news reporting practice aided by Information and Communication Technology (ICT). The research aims to demonstrate the effectiveness of news reporting as a method to improve students' speaking abilities, leveraging ICT tools such as video creation and platforms like "Flipgrid." Various challenges inhibiting students' progress in speaking English, such as lack of confidence, pronunciation differences, limited vocabulary, and grammar issues, are discussed. The study at Jin Seung High School focuses on assessing students' speaking skills through questionnaires and implementing interventions using video-based learning facilitated by ICT tools. The research questions revolve around the potential development of speaking skills through news reporting in ICT and the impact of ICT on students' mastery of speaking skills. The findings showed that Flipgrid effectively enhances high school students' English-speaking skills by providing a time-efficient, easy-to-use platform that boosts confidence and reduces anxiety. However, further research with larger samples and objective proficiency measures is needed to confirm these findings and address technical issues.